Effects of Imposed Damage on the Capillary Water Absorption of Recycled Aggregate Concrete - Qi Gao; Zhiming Ma; Jianzhuang Xiao; Fuan Li (Advances in Materials Science and Engineering)
Capillary water absorption of concrete is closely related to its pore structure, permeability, and durability. This paper intensively investigates the effects of imposed damage, including freeze-thaw damage and loading damage, on the capillary water absorption of recycled aggregate concrete (RAC). Freeze-thaw cycle test, loading test, and the experiment of capillary water absorption were carried out, respectively. The results demonstrate that the addition of recycled coarse aggregate (RCA) results in the increase in the capillary absorption behavior of RAC without imposed damage, and there exists a linear correlation between the behaviors of capillary water absorption and chloride penetration of RAC. The imposed freeze-thaw damage or load damage of RAC boosts with the increase of RCA replacement percentages after suffering the same freeze-thaw cycles or loading level. The imposed freeze-thaw damage and load damage further lead to the increase in the capillary water absorption of RAC, and the capillary absorption coefficient of RAC increases linearly with the increased RCA replacement percentages, after suffering the same freeze-thaw cycles or loading level. Furthermore, capillary absorption coefficient increases linearly with the growth of imposed freeze-thaw damage or load damage degree, which can be used to estimate the capillary absorption behavior of RAC exposed to the extreme environment.